The Issue of Disciplinarity and Non-disciplinarity of Tourism Studies - BUTOWSKI, Leszek (Téoros)

(untitled) (Université du Québec à Montréal, 2016)
This paper is devoted to the developments concerning the issue of disciplinarity and non-disciplinarity of tourism studies. The topic is embedded in a wider context of the academic identity of the community of tourism researchers. As the theoretical foundations for the discussion some concepts of non-classical sociology of science (rooted in Thomas Kuhn’s theory of development of science and ideas of the “Strong Programme”) were used. In order to analyze the problem theoretically and empirically, a three-stage research framework was adopted, commencing with a directed review of Anglo-American and Francophone literature, followed by a survey of a purposeful sample of tourism academics and concluding with a further analysis of the literature, this time confronting empirical findings with the identified scholars’ stances. The empirical research included a survey carried out among approximately 270 scholars of tourism from almost 50 countries from all the continents.